The Everyday Aesthetics of Public Space - Mateusz Salwa (Acta Universitatis Lodziensis: Folia Philosophica, 2019)
The main claim of the article is that everyday aesthetics conceived as a philosophical analysis of everyday objects and situations offers a theoretical perspective that may be applied to the aesthetics of public space. Analysed in aesthetic terms, the public space may be thought to be a space that offers an aesthetic experience to the widest possible public. I contend that the aesthetic quality of public space should be a quality that favours positive experiences of the everyday, banal practices taking place in it. Accordingly, designing public space should consist in making it “everyday experience-friendly.” My argument will be illustrated by the example of a site-specific installation, the Oxygenator, created in Warsaw by Joanna Rajkowska, whose intention was to offer people an ordinary place where they could meet in a “healthy atmosphere.”